Reversion of QuantiFERON-TB Gold In-Tube test in individuals with and without prophylactic treatment for latent tuberculosis infection: A systematic review and meta-analysis. Issue 4 (October 2018) - Zhang, Haoran; Xin, Henan; Li, Xiangwei; Li, Hengjing; Li, Mufei; Feng, Boxuan; Gao, Lei
Highlights: QFT reversion was frequently observed in serial tests. Summarized QFT reversion rates were found to be similar among individuals with and without preventive treatment. Serial QFT testing might be inappropriate for evaluating preventive treatment efficacy. Summary: Objectives: Reversion of tuberculosis (TB) infection testing has been suggested to be associated with prophylactic treatment efficacy. However, evidences based on randomized controlled study were sparse. Methods: Studies on serial QuantiFERON-TB Gold In-Tube (QFT) test, among individuals with and without prophylactic treatment were identified in the databases of PubMed, MEDLINE and EMBASE up to 28 February 2018. The reversion rates were quantitatively summarized by means of meta-analysis using the random-effect model. Results: A total of 52 eligible studies were included in the meta-analysis on QFT test reversion rate among participants with (20 studies) and without (32 studies) prophylactic treatment. Summarized reversion rate was found to be 24.9% (95% confidence interval [CI]: 18.4–32.9%) and 25.3% (95% CI: 19.6–32.0%) for those completed or without treatment, respectively. When the analysis was restricted to the participants completed treatment, higher summarized rate of QFT reversion was found among those with longer course therapy (9INH vs. the other regimens), studies from Asia (vs. Europe and America), and individuals with immunosuppression disorders (vs. general populations). Conclusions: Our results suggested that QFT reversion was frequently observed regardless of with or without prophylactic treatment. Serial QFT testing might be inappropriate for evaluating preventive treatment efficacy.